Methodologies for data collection in congenital haemophilia with inhibitors (CHwI): critical assessment of the literature and lessons learned from recombinant factor VIIa. Issue 4 (9th May 2018) - Kessler, C. M.; Benchikh el Fegoun, S.; Worster, A.
Abstract : Aims: To systematically review the effectiveness of on‐demand treatment with recombinant coagulation factor VIIa (rFVIIa) in congenital haemophilia with inhibitors and, if feasible, perform a meta‐analysis of the data. Materials and methods: Publications from Embase ®, MEDLINE ®, MEDLINE ® In‐Process and the Cochrane Central Register of Controlled Trials were searched. Selected publications were reviewed for inclusion by two independent expert reviewers. Discrepancies were reconciled by a third independent reviewer. Data from selected studies were extracted using a predefined grid to ensure uniform and comparable results were captured. Results: A systematic search (cut‐off date of 2 May 2016) identified 20 studies (13 observational; seven randomized controlled trials). All studies were of sufficient quality to include in this analysis and comprised 1221 participants, with 5981 bleeds in 746 individuals treated with rFVIIa. Haemostatic overall effectiveness of the individual studies identified ranged from 68% to 100% at ≤12 hours, 86% to 96% at 13‐24 hours and 76% to 99% at 24‐48 hours with rFVIIa <100 μg/kg, with similar rates reported for the ≥250 μg/kg dose. However, heterogeneity between the studies precluded pooling of results. Conclusions: Data from the individual studies confirmed that rFVIIa is an effective therapy for the on‐demand treatment of bleeds in congenital haemophilia with inhibitors. However, the high levels of heterogeneity between studies precluded pooling of results for a valid, reliable or precise summary measure. There remains a need to implement standardized clinical definitions and measurements for the effectiveness and safety of haemophilia therapies in future clinical trials.